Sub-watt power triboelectric generator via polarization switching charge carrier. (1st December 2022) - Chung, Seh-Hoon; Cha, Kyunghwan; Song, Myunghwan; Kim, Dongchang; Heo, Deokjae; Kim, Min-Kun; Jung, Heesoo; Jin, Youngho; Hong, Jinkee; Chung, Jihoon; Lee, Sangmin
Abstract: Triboelectric nanogenerator (TENGs) is one of the promising energy harvesting methods, and is expected to serve as primary power source. Nevertheless, previous TENGs were only able to generate low-current outputs. Even when energy management systems (EMSs) are used for TENGs, electrical losses occurred owing to complicated EMS circuits. Accordingly, high-mechanical inputs were still necessary to match power levels for existing electronics. Therefore, film capacitor-based charge-carrier TENGs (FCC-TENGs) are fabricated herein. These can be easily utilized for various circuits owing to their ultrahigh output with low input. As film capacitor-covered charge-carrier cylinders are rolling, FCC-TENGs can produce high voltage and current outputs of about 5000 V and 10 A, respectively, and can effectively reduce friction and wear. By loading external load, the root mean square power of FCC-TENG is measured up to 720 mW. Given the generated outputs, FCC-TENG can be used as primary power source for several power supply circuits that can turn on 12 commercial 5 W light-emitting diodes, power electric device, and charge lithium-ion battery. Graphical Abstract: ga1 Highlights: Can produce ultrahigh electrical outputs of about 5000 V and 10 A and generate RMS power of 720 mW with external load. Easily optimized by using a simple energy management system circuit. Effectively reduce friction and wear by rolling film capacitor covered charge-carrier cylinders. Hand-operatable device that can turn on LEDs, power electric device, and charge lithium-ion battery.